2018
DOI: 10.1152/ajpendo.00224.2017
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-specific deletion of Zfp36 protects against insulin resistance and fatty liver in diet-induced obese mice

Abstract: Obesity is associated with adipose tissue inflammation that contributes to insulin resistance. Zinc finger protein 36 (Zfp36) is an mRNA-binding protein that reduces inflammation by binding to cytokine transcripts and promoting their degradation. We hypothesized that myeloid-specific deficiency of Zfp36 would lead to increased adipose tissue inflammation and reduced insulin sensitivity in diet-induced obese mice. As expected, wild-type (Control) mice became obese and diabetic on a high-fat diet, and obese mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 76 publications
(101 reference statements)
0
20
0
Order By: Relevance
“…Consequently, modulating TTP might provide a promising avenue for the development of inflammation regulatory therapies. Specifically, therapeutic approaches to increase the TTP activity can be expected to ameliorate the course of numerous chronic inflammatory diseases with a previously shown connection to TTP, such as rheumatoid arthritis [ 108 , 114 , 115 ], atherosclerosis [ 116 ], diabetes [ 117 ], inflammatory bowel disease [ 118 ], chronic obstructive pulmonary disease [ 119 ], and autoimmune diseases [ 108 , 120 ]. Since chronic inflammatory diseases are a major health care burden, such approaches appear extremely appealing.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, modulating TTP might provide a promising avenue for the development of inflammation regulatory therapies. Specifically, therapeutic approaches to increase the TTP activity can be expected to ameliorate the course of numerous chronic inflammatory diseases with a previously shown connection to TTP, such as rheumatoid arthritis [ 108 , 114 , 115 ], atherosclerosis [ 116 ], diabetes [ 117 ], inflammatory bowel disease [ 118 ], chronic obstructive pulmonary disease [ 119 ], and autoimmune diseases [ 108 , 120 ]. Since chronic inflammatory diseases are a major health care burden, such approaches appear extremely appealing.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil degranulation [52], innate immune system [53], platelet degranulation [54], extracellular matrix organization [55], diseases of glycosylation [56], platelet activation, signaling and aggregation [57], hemostasis [58], secretion [59], secretory vesicle [60], transmembrane transporter activity [61], cell adhesion [62], localization of cell [63], extracellular matrix [55], intrinsic component of plasma membrane [64], structural molecule activity [65], signaling receptor binding [66], have been highly noted in T2DM. Reports indicate that HIF1A [67], HLA-DRB1 [68], CHI3L1 [69], ADORA2A [70], ADRB2 [71], CLU (clusterin) [72], AGT (angiotensinogen) [73], VCAM1 [74], PPARA (peroxisome proliferator activated receptor alpha) [75], APOL1 [76], ZFP36 [77], PPM1B [78], SOCS1 [79], SNCA (synuclein alpha) [80], CTSS (cathepsin S) [81], IL6R [82], CFB (complement factor B) [83], DEFB1 [84], VNN1 [85], RAB27A [86], DPP4 [87], RARRES2 [88], CASP1 [89], LCN2 [90], REG3A [91], CD74 [92], PCSK2 [93], CHGB (chromogranin B) [94], TTR (transthyretin) [95], LRG1 [96], ALB (albumin) [97], DPP7 [98], APOH (apolipoprotein H) [99], CTSD (cathepsin D) [100], GCG (glucagon) [101], KCNQ1 [102], NR4A1 [103], PLIN5 [104], ALDH2 [105], ANG (angiogenin) [106], CLDN7 [107], PRLR (prolactin receptor) [108], SOD2 [109], MLXIPL (MLX interacting protein like) [110], CTSD (cathepsin D) [111], PECAM1 [112], ADA (adenosine deaminase) [113], MFGE8 [114], COL1A1 [115], COL3A1 [116], NID2 [117], ARG1 [118], CD93 [119], IGF2 […”
Section: Discussionmentioning
confidence: 99%
“…Another study found that insulin resistance in obese mice was associated with enhanced Zfp36 expression in the hepatic macrophage (m1). The study of Caracciolo, V. et al, revealed that the myeloid-speci c deletion of Zfp36 protects against insulin resistance and fatty liver in mice whose obesity is diet-induced (27). Moreover, a signi cant correlation has been reported between TTP and hepatocarcinogenesis (28).…”
Section: Discussionmentioning
confidence: 99%